Tega Industries Ltd. Part B : journey of an Indian MNC - Singla, Chitra; Singh, Bulbul, active 2020 (London : Indian Institute of Management, Ahmedabad, 2020)
Tega Industries Ltd-an Indian multinational company that mainly designed, produced, and distributed non-metallic mill liners-acquired Acotec in Chile in 2011 and renamed it Tega-Acotec SA. Tega-Acotec was profitable for the first two years, after which it bled cash year after year, resulting in a cumulative loss of INR 2.5 billion by March 2016. In January 2016, Madan Mohanka (MM, the founder), Mehul Mohanka (his son), and Syed Yaver Imam (Director of Marketing, Tega Industries) were contemplating closing down the subsidiary. However, they decided to give the company one more chance for revival by exploring the market for small mill liners, Tega's core product, which they had not yet explored in Chile. They also took some crucial measures to turn it into a profitable unit. After four years of hiring new employees, innovating a new product, and inculcating the right culture and practices, Tega-Acotec started showing positive signs of revival in 2019. However, in January 2020, the COVID-19 crisis hit the world and Chile experienced political unrest at the same time, leading to a bit of uncertainty about Tega-Acotec's future. MM, who had turned 77 in 2020, wondered whether this subsidiary would ever enable him to achieve his goal of making it the highest-profit centre in Tega Industries' group of companies and leading Tega to the second or third position in the global mill-lining industry. This uncertainty triggered another dilemma for MM-should he invest another INR 1.25 billion in Tega-Acotec to scale up its operations or sell it off while it was profitable?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies; Business planning -- Case studies; Consolidation and merger of corporations -- Case studies; International business enterprises -- Case studies